The transformative materiality of meaning-making - Parkin, David (Encounters, 2021)
This book explores verbal and non-verbal communication from a social anthropological viewpoint, drawing on ethnographic data from fieldwork in eastern Africa. It gives an overview of developments since the 1960s in the anthropology of language use and how these have influenced the author's thinking